Cognitive decline affects diabetic women - Perzyński, Adam; Chmiel-Perzyńska, Iwona (Current Problems of Psychiatry, 2017)
Introduction: DM provokes peripheral complications and changes in central nervous system. Central changes in the course of diabetes mellitus (DM) include changes in brain tissue structure, electrophysiological abnormalities but also disturbances in neurotrans-mission leading to cognitive decline. Aim of the study: The aim of our study was to asses cognitive functioning of patients suffering from DM1 for at least 5 years but without any diagnosed complications. Materials and methods: Cognitive functions were assessed in 59 patients (35 men) with Trail Making Test A (TMT A) and B (TMT B), Maze Test (MT), Stroop Test (SCWT) and Rey Auditory Verbal Learning Test (RAVLT). Mental disorders were excluded with Beck’s Depression Inventory (BT), Mini Mental State Examination (MMSE) and psychiatric examination. Results: We stated that women, compared with men, presented worsening of executive functions, speed and motor control. Cognitive decline depended on number of episodes of at least moderate hypoglycemia and duration of disease. HbA1c below 8% resulted in better memory, speed and motor control. Cognitive decline was more escalated in the patients with atherogenic lipid profile. Conclusions: It seems that even apparent lack of complications is not unambiguous with lack of cognitive decline and women seem to be more susceptible. DM1 affects young individuals, whose cognitive functions are in the course of the development, so it is important to find the underlying mechanisms and the areas of disturbed cognitive functioning and further investigations are needed.